COVID-19 Pandemic and Vulnerability in Private Educational Sector Employment in Ghana: A Study of Three Municipalities in the National Capital - Juliana Abagsonema Abane; Ernest Yeboah Asamoa (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
The study investigated how the Government of Ghana’s educational policies during COVID-19 had excluded private school teachers and contributed to their vulnerability. The study was a descriptive cross-sectional survey. The population was private school teachers in Ghana. Non-probability sampling technique was used to select the sample size. The cluster sampling technique was adopted to select one municipality in the Greater Accra region: based on the recorded number of COVID-19 cases and economic activities. The study involved 150 private school teachers. The analytic tool used in the analysis is inferential and descriptive statistics. The study found that COVID-19 severely impacted private school teachers' livelihood and income stream in the selected municipalities despite government intervention policies. The study recommends that political leadership, as well as the management of private school teachers, should develop innovative systems that will serve as safety nets for future crises. Keywords: Education policy, vulnerability, private school teachers, COVID-19 pandemic Studi ini membahas bagaimana kebijakan pendidikan Pemerintah Ghana selama COVID-19 telah mengeksklusi guru sekolah swasta dan berkontribusi pada kerentanan mereka. Penelitian ini merupakan penelitian deskriptif cross-sectional survey. Populasi dalam penelitian ini adalah guru sekolah swasta di Ghana. Teknik non-probability sampling digunakan untuk memilih ukuran sampel. Teknik pengambilan sampel klaster diadopsi untuk memilih satu kota di wilayah Greater Accra: berdasarkan jumlah kasus COVID-19 yang tercatat dan kegiatan ekonomi. Penelitian ini melibatkan 150 guru sekolah swasta. Alat analisis yang digunakan dalam analisis adalah statistik inferensial dan deskriptif. Hasil penelitian menunjukkan bahwa COVID-19 sangat berdampak pada mata pencaharian dan sumber pendapatan guru sekolah swasta di kota-kota tertentu meskipun ada kebijakan intervensi pemerintah. Studi ini merekomendasikan bahwa kepemimpinan politik, serta manajemen guru sekolah swasta, harus mengembangkan sistem inovatif yang akan berfungsi sebagai jaring pengaman untuk krisis di masa depan. Kata kunci: Kebijakan pendidikan, kerentanan, guru sekolah swasta, pandemi COVID-19